IMPLEMENTASI DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN JD.id Jakarta - Glen Irwinto Laluyan; Imam Wibowo; Amanda Setiorini (Jurnal Manajemen Bisnis Krisnadwipayana, 2019)
This research is about Implementation of Digital Marketing on Consumers Purchasing Decisions. This research aims to analize the implementation of the Social Media Marketing, Pay Per Click and Email Marketing to the Purchasing Decisions of Jakarta JD.id Consumers. In this research the sample took 100 respondent using purposive sampling technique, which respondent is an active user of the face book forum and has shopped on the JD.id site. The data that has been obtained tested using multiple linear regression analysis technique. The result that shown from this research are Social Media Marketing, Pay Per Click and Email Marketing simultaneous and partial gave positive and significant effect to Consumers Purchasing Decisions.